2010
DOI: 10.1111/j.1600-0765.2009.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on the effect of rinsing with povidone-iodine during nonsurgical periodontal therapy

Abstract: The existing literature is inconsistent regarding whether there is any additional effect of povidone-iodine (PVP-iodine) as an adjunctive to scaling and root planing, and, if there is an effect, what its size is. Therefore, the aim of this study was to assess the additional effect of PVP-iodine as an adjunct to scaling and root planing compared with water, saline or no rinse in the treatment of chronic periodontitis. Material and methods: An electronic literature search of the databases PubMed, EMBASE and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 47 publications
(112 reference statements)
1
36
0
1
Order By: Relevance
“…Here, different baseline results for several bacterial species, such as A. actinomycetemcomitans, P. gingivalis , or T. denticola , could also mask some advantages of povidone–iodine. The findings of our study correspond with the systematic review by Sahrmann et al, 47 where a small to moderate clinical significance of the use of povidone–iodine was described. Our study also shows that SRP of high quality and under good conditions cannot be improved further by additional means during treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Here, different baseline results for several bacterial species, such as A. actinomycetemcomitans, P. gingivalis , or T. denticola , could also mask some advantages of povidone–iodine. The findings of our study correspond with the systematic review by Sahrmann et al, 47 where a small to moderate clinical significance of the use of povidone–iodine was described. Our study also shows that SRP of high quality and under good conditions cannot be improved further by additional means during treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Another systematic review found no significant benefit from supplementing full-mouth debridement with chlorhexidine irrigation [68]. A recent systematic review specifically addressed rinsing with povidone-iodine during nonsurgical periodontal therapy [69]. A small but statistically significant beneficial effect of pocket rinsing in terms of probing depth reduction was found.…”
Section: What Is the Optimal Administration Pathway?mentioning
confidence: 99%
“…A recent systematic review on this topic showed evidence for an improved therapeutical effect regarding pocket depth reduction, when PVP-iodine was used during scaling and root planing [30].…”
Section: Introductionmentioning
confidence: 99%